Spreading the Word: Investigating Antecedents of Consumers' Positive Word-of-Mouth Intentions and Behaviors in a Retailing Context - Brown, T. J. (Journal of the Academy of Marketing Science, 2005)
Empirical studies investigating the antecedents of positive word of mouth (WOM) typically focus on the direct effects of consumers' satisfaction and dissatisfaction with previous purchasing experiences. The authors develop and test a more comprehensive model of the antecedents of positive WOM (both intentions and behaviors), including consumer identification and commitment. Specifically, they hypothesize and test commitment as a mediator and moderator of satisfaction on positive WOM and commitment as a mediator of identification on WOM. Using data obtained from customers of a retailer offering both products and services, they find support for all hypothesized relationships with WOM intentions and/or WOM behaviors as the dependent variable. The authors conclude with a discussion of their findings and implications for both marketing theory and practice. [PUBLICATION ABSTRACT]